INVESTIGATION ON THE PERFORMANCE OF FLAXSEED BIODIESEL BLENDS WITH TIO2 COATED PISTON ON A FOUR STROKE DI DIESEL ENGINE (Journal of Mechanical Engineering, 2017)
Diesel engines are being used extensively for fuel economy but due to gradual depletion of Petroleum resources and increase in exhaust emissions, there is an urgent need for suitable alternative fuels for the diesel engines. As our country is an agricultural country, if the alternate fuels are produced by our farmers it will be beneficial for the country and the farmers also. In recent studies, researchers studied various vegetable oils like canola oil, alovera oil, soya been oil, flaxseed oil and hone oil etc. Out of all flaxseed oil play an important role as an alternative fuel. But the properties of flaxseed oil are not suitable for the usage in the existing diesel engines without blending with diesel fuel. The performance of the engine depends on the combustion phenomenon and it further depends on the amount of heat retained in the combustion chamber. Hence the present work is planned accordingly to develop an insulated engine by coating the piston with TIO2material. So that more amount of heat will be retained in the combustion chamber which aids the combustion. Further the performance of flaxseedbiodiesel blend namely B10, B20, B30 and B40 are tested and the results are mentioned accordingly.